Prevalence of Giardia duodenalis in the “CEIBA” animal welfare center, Rionegro, Colombia (2017) (Orinoquia, 2020)
To determine the prevalence of Giardia duodenalis parasitism at the CEIBA wellness center in the municipality of Rionegro, Colombia, during June 2017. A descriptive cross-sectional, non-experimental, randomized study was carried out. 112 coprological evaluations of canines of the “CEIBA” wellness center of both sexes, all ages and commercial feeding were evaluated. They were submitted to a cochrological evaluation, by direct extraction of rectal ampulla and evaluated in the Clinical Laboratory of the University of Lasallian Hospital “Hno Marco Antonio Serna, fsc”, two diagnostic methods were carried out, flotation with saturated saline solution (Willys Molloy) and direct smears. The presence of Giardia duodenalis was categorized as 0-3 crosses. A total of 60 (55%) samples were present, with 10 (8.92%) infested by Giardia duodenalis, accounting for 16.66% of the total parasite, for a cross 2 (20%), with two crosses 5 (50%) and three 3 (30%). The prevalence of Giardia duodenalis in the CEIBA well-being center is low with respect to prevalence data in other canines or hostels, which may be influenced by disease prevention and control measures.
Keywords: canine; giardiasis; parasitism; intestinal protozoan